Pengaruh Efikasi Diri, Kepuasan Kerja, dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan PT Indopack Mandiri Sukses - Inna Nisawati Mardiani; Sinta Eka Sari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the influence of self-efficacy, job satisfaction, and non-physical work environment on employee performance at PT Indopack Mandiri Sukses using a quantitative explanatory approach. The research adopts a census sampling technique involving 57 employees, with data collected through structured questionnaires and analyzed using multiple linear regression. The findings indicate that self-efficacy has a positive and significant effect on employee performance by enhancing individual confidence in task completion. Job satisfaction also demonstrates a significant contribution by reflecting employees’ positive emotional evaluation toward their work, which supports consistent performance outcomes. Furthermore, the non-physical work environment emerges as the most dominant factor influencing performance, particularly through interpersonal relationships, effective communication, and organizational support. These results highlight the importance of integrating psychological and organizational environm.